(Applied study of a selected sample of companies listed in the - Shellan Kazom Suza Ali; Shatha Abdul-Hussein Jabr; Ahmed Talib Abdel Amir (Journal of Madenat Alelem University College, 2024)
The current research aims to evaluate common stocks and form their optimal portfolio using the pricing of capital assets to identify the level of improvement in the investment portfolio formed according to traditional methods in order to assist in making investment decisions in the Iraqi market for securities. The research sample and the research community included all sectors in the Iraqi market for securities, and the research sample consisted of (22) companies that met the search conditions for the period (2016-2020).                   The research concluded that the analysis of the market value of the shares of the research sample resulted from a clear fluctuation in these values ​​as a result of the continuous changes in stock prices and all the companies of the research sample were also characterized by high risks, and this was reflected by the beta coefficient of the stock, which appeared to be higher than the market risks, and this reflects the degree of sensitivity  The high returns of the shares of all companies in the direction of the change in the market return, and this shows the reason for the high volatility of the returns of the shares of companies, and then the high risk, and therefore these shares are described as risky shares. From the analysis of the real value of the shares of the companies, the research sample according to the cash flow model, the pricing discrepancy for the prices of companies’ shares, as  All companies were far from the true value, and this reflects the science of the ability of this model to explain stock prices.